2020
DOI: 10.1016/j.heliyon.2020.e05701
|View full text |Cite
|
Sign up to set email alerts
|

Seed bio-priming with tri-species consortia of phosphate solubilizing rhizobacteria (PSR) and its effect on plant growth promotion

Abstract: Three potential rhizobacteria namely Burkholderia gladioli (MTCC 10216), Pseudomonas sp. (MTCC 9002) and Bacillus subtilis (MTCC 8528) procured from IMTECH, Chandigarh (India) were evaluated individually and as consortia for its phosphate (P) solubilizing ability and effect of growth of fenugreek ( Trigonella foenum-graecum L.) and tomato ( Lycopersicon esculentum L.). Phosphate solubilizing abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 44 publications
0
7
0
2
Order By: Relevance
“…In a P-deficient tropical soil, priming of mung bean seeds with 0.01 and 0.02% P enhanced the P uptake (Shah et al, 2012). Kumar et al (2020) reported maximum P solubilizing activity in a consortium of Burkholderia gladioli, Pseudomonas sp., and Bacillus subtilis, and the application of this consortium through seed biopriming improved the soil available P by 54%.…”
Section: Practices and Performances Of Seed Primingmentioning
confidence: 96%
“…In a P-deficient tropical soil, priming of mung bean seeds with 0.01 and 0.02% P enhanced the P uptake (Shah et al, 2012). Kumar et al (2020) reported maximum P solubilizing activity in a consortium of Burkholderia gladioli, Pseudomonas sp., and Bacillus subtilis, and the application of this consortium through seed biopriming improved the soil available P by 54%.…”
Section: Practices and Performances Of Seed Primingmentioning
confidence: 96%
“…Kemampuan endo-rhizobakteri dalam meningkatkan kecepatan tumbuh relatif dan T 50 disebabkan oleh kemampuan agens hayati tersebut dalam memacu perkecambahan benih. Kumar et al (2020) melaporkan bahwa inokulasi campuran BPF + Azotobacter sp. + Azospirilum sp.…”
Section: Hasil Dan Pembahasanunclassified
“…mampu meningkatkan indeks vigor benih secara signifikan dibandingkan dengan tanpa inokulasi (kontrol). Kumar et al (2020) melaporkan bahwa konsorsium mikroba juga mampu meningkatkan perkecambahan benih dan pertumbuhan tanaman fenugreek dan tomat. Lebih lanjut, Saputra et al (2020) melaporkan bahwa perlakuan campuran agens hayati mampu meningkatkan viabilitas dan vigor benih cabai rawit lokal.…”
unclassified
“…For the last six years researchers are working on designing rhizobacterial consortium for enhancing plant growth, their yield of production, soil health, as a biocontrol agent, and stabilizing the rhizobacterial interactions ( Kamalnath et al, 2019 ; Swandi et al, 2019 ; Asyiah et al, 2020 ; Kumar et al, 2020 ; Shang and Liu 2020 ; Vaid et al, 2020 ; Redondo-Gómez et al, 2021 ; Karuppiah et al, 2022 ; Shabaan et al, 2022 ) In the current review, the authors have emphasized the role of rhizosphere microbes in PGP activities. Moreover, the authors have also highlighted the recent trends in PGPR-based research works.…”
Section: Introductionmentioning
confidence: 99%